2020
DOI: 10.7717/peerj.10034
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of Gyps coprotheres (Aves, Accipitridae, Accipitriformes): phylogenetic analysis of mitogenome among raptors

Abstract: Three species of Old World vultures on the Asian peninsula are slowly recovering from the lethal consequences of diclofenac. At present the reason for species sensitivity to diclofenac is unknown. Furthermore, it has since been demonstrated that other Old World vultures like the Cape (Gyps coprotheres; CGV) and griffon (G. fulvus) vultures are also susceptible to diclofenac toxicity. Oddly, the New World Turkey vulture (Cathartes aura) and pied crow (Corvus albus) are not susceptible to diclofenac toxicity. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…1 ). As previously observed in partial mtDNA sequences 35 , NW vultures exhibited the ancestral avian gene order, while OW species differed from the standard arrangement due to the presence of a pseudo control region 14 , 52 54 . The overall base composition of condors was similar (A = ~31%, T = ~23%, C = ~32%, G = ~13%), showing a slight A + T bias for most regions, except ND6 that showed a marked C + G bias, similar ( r > 0.9; P < 0.001 in all cases) to other vultures (Figure S1 ).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…1 ). As previously observed in partial mtDNA sequences 35 , NW vultures exhibited the ancestral avian gene order, while OW species differed from the standard arrangement due to the presence of a pseudo control region 14 , 52 54 . The overall base composition of condors was similar (A = ~31%, T = ~23%, C = ~32%, G = ~13%), showing a slight A + T bias for most regions, except ND6 that showed a marked C + G bias, similar ( r > 0.9; P < 0.001 in all cases) to other vultures (Figure S1 ).…”
Section: Resultssupporting
confidence: 77%
“…Our analysis of PCGs in condors showed that COX3, ND4 and CYTB, share the same transcriptional exceptions of Turkey vultures, where TAA stop codon is completed by the addition of two 3' A residues to the mRNA. This exception has been reported for COX3, ND2 and ND4 in the Griffon (Gyps fulvus) and Cape (Gyps coprotheres) vultures 53,54 , and for ND2 in the Cinereous vulture and Himalayan griffon 14,52 . In addition, we found a frameshift in the ND3 gene of both condors, suggesting an alternative reading of mitochondrial mRNA.…”
Section: Resultsmentioning
confidence: 78%
“…The assembled transcriptome was converted to a local Blast database and OAT1 and OAT2 sequences were identified based on the predicted sequences from the Golden Eagle OAT1 (XM_011601043.1) and OAT2 (XM_011585794.1). The Golden Eagle was selected since the two species have been shown to be closely related [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The eyes of raptors have been analyzed, revealing visual mechanisms that have been applied to the field of optics (Snyder and Miller, 1978 ). As for other non-chicken bird models, research in birds of prey is being facilitated by advances in understanding of their genomics and transcriptomics (Bartholomew and Tucker, 1963 ; Zhan et al, 2013 ; Pan et al, 2017 ; Kang et al, 2018 ; Cho et al, 2019 ; Doyle et al, 2019 ; Adawaren et al, 2020 ). Interestingly, modern day falconry (training and hunting with raptors) offers an excellent opportunity for research on topics that require conditioning or problem-solving skills in non-mammalians, including the development of such skills.…”
Section: Alternative Avian Models For Research In Developmentmentioning
confidence: 99%